Visual modality research in virtual and mixed reality simulation. (October 2015) - Stevens, Jonathan; Kincaid, Peter; Sottilare, Robert
Military organizations worldwide continue to invest heavily in research, development, and fielding of virtual and mixed reality simulations and simulators for training. However, the future fiscal environment will be challenging for both simulation as well as the US Army as a whole. Thus, wise design decisions must be made when developing virtual simulations for training. In order to optimize the effectiveness of these simulations, developers must employ trade-off analysis and scientific methods to derive empirical evidence, in order to ensure that the simulation under development is optimized to meet the training requirements, while still adhering to cost and schedule constraints. This paper specifically focuses on the task of employing the optimal visual modality in virtual and mixed reality simulations. This paper reviews the literature on training simulation benefits and taxonomy, and examines the training efficacy of virtual and mixed reality simulation. Major concepts and applications of virtual and mixed reality simulation training efficacy are discussed. A key component of virtual simulation, visual modality, is examined through a literature review and recommendations for visual display design parameters are provided.